YTHDF1‐mediated translation amplifies Wnt‐driven intestinal stemness. (17th February 2020) - Han, Bing; Yan, Sujun; Wei, Saisai; Xiang, Jie; Liu, Kangli; Chen, Zhanghui; Bai, Rongpan; Sheng, Jinghao; Xu, Zhengping; Gao, Xiangwei
Abstract: N6‐methyladenosine (m 6 A) mRNA methylation has emerged as an important player in many biological processes by regulating gene expression. However, its roles in intestinal stem cell (ISC) homeostasis remain largely unknown. Here, we report that YTHDF1, an m 6 A reader, is highly expressed in ISCs and its expression is upregulated by Wnt signaling at the translational level. Whereas YTHDF1 is dispensable for normal intestinal development in mice, genetic ablation of Ythdf1 dramatically blocks Wnt‐driven regeneration and tumorigenesis with reduced ISC stemness. Mechanistically, YTHDF1 facilitates the translation of Wnt signaling effectors including TCF7L2/TCF4, while this process is enhanced during Wnt activation to augment β‐catenin activity. Targeting YTHDF1 in ISCs of established tumors leads to tumor shrinkage and prolonged survival. Collectively, our studies unveil YTHDF1 as an amplifier of Wnt/β‐catenin signaling at the translational level, which is required for the maintenance of ISCs during regeneration and tumorigenesis. Synopsis: YTHDF1, an m6A reader, is dispensable for normal intestinal development but required for Wnt‐driven regeneration and tumorigenesis. YTHDF1 facilitates the translation of Wnt signaling effectors to regulate intestinal stem cell activity. YTHDF1 is highly expressed in intestinal stem cells and regulated by Wnt signaling. YTHDF1 is required for Wnt‐driven regeneration and tumorigenesis. YTHDF1 promotes stemness of intestinal stem cells. YTHDF1 facilitates the translation of Wnt signaling effectors to augment β‐catenin activity. Abstract : YTHDF1, an m6A reader, is dispensable for normal intestinal development but required for Wnt‐driven regeneration and tumorigenesis. YTHDF1 facilitates the translation of Wnt signaling effectors to regulate intestinal stem cell activity.